The Disguising at Hertford - Lydgate, John (Salt Lake City, UT : Project Gutenberg, 2001)
"The Disguising at Hertford" by John Lydgate is a verse play written around the early 15th century, likely during the late medieval period. This theatrical work explores themes of marriage and domestic discord through a humorous lens, showcasing the trials and tribulations faced by husbands under the rule of their strong-willed wives. Set against the backdrop of royal festivities at Hertford Castle, the play is a lively examination of gender dynamics and the nature of power in marital relationships. The plot unfolds as a group of husbands presents a complaint to the king, expressing their grievances about the domineering behavior of their wives. Each husband shares his amusing woes, illustrating the challenges of marriage and the social expectations placed upon both men and women. The wives, responding with equal fervor, assert their own perspectives and rights, adding a layer of complexity to the dialogue. The king, acting as an impartial judge, refrains from delivering an immediate judgment, prompting a deeper exploration of the societal norms surrounding marriage and authority. Ultimately, the play$1 (Bs resolution invites the audience to reflect on the balance of power within domestic life, wrapped in the comedic exchanges between the characters. (This is an automatically generated summary.)s
Release date is 2001-10-01
Produced by: An Anonymous Volunteer and David Widger
Keywords: Comedy; Marriage -- Drama; England -- Drama